Reclamação constitucional no processo do trabalho: hipóteses de cabimento - Santos, Ailton Vieira dos (2019)
The purpose of this dissertation is to carry out a theoretical study on the constitutional complaint within the scope of Brazilian labor courts. The study starts with a systematic analysis of the Brazilian legal system from the perspective of the evolution of the constitutional complaint doctrine and the impact caused by the Brazilian Code of Civil Procedure of 2015, which introduced new situations when the constitutional complaint is admissible, and by the provision of use of the constitutional complaint before all Brazilian appellate courts and its compatibility and suitability to labor proceedings, especially after the Labor Reform (Federal Act No. 13,427/2017). The relevance of this paper emerges from the aim of establishing a link between the historical aspects of the constitutional complaint, the rules of civil and constitutional procedures that govern the subject, and procedural labor law, which is done in order to allow proper use of the constitutional complaint in the search for effective judicial performance. To do so, the subject of the expository theoretical-dogmatic exam is the origin and historical evolution of the constitutional complaint, its contextualization and development in labor procedure, the controversy about its legal nature, all the situations when the constitutional complaint is admissible in labor proceedings, and Labor Courts precedents on the matter